Analysis of Text Classification Methods - Kolevski, Goran; Madevska Bogdanova, Ana (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2011)
The goal of this paper is to describe the problem of text document classification as well as to analyze some of the most common methods that are being used for its resolution. There are numerous practical examples where according to some provided document corresponding class of it is required to be assigned. There are a lot of documents that are already classified by some expert from the particular field thus the idea of this paper is to show how such classification can be used to train a system to classify newly provided documents.